2022
DOI: 10.1186/s12931-022-02087-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of bronchoalveolar lavage in children with persistent wheezing

Abstract: Background Recent studies have demonstrated the important role of metabolomics in the pathogenesis of asthma. However, the role of lung metabolomics in childhood persistent wheezing (PW) or wheezing recurrence remains poorly understood. Methods In this prospective observational study, we performed a liquid chromatography/mass spectrometry-based metabolomic survey on bronchoalveolar lavage samples collected from 30 children with PW and 30 age-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Tan et al found that serum levels of L-palmitoylcarnitine were signi cantly decreased in a rat model of myocardial infarction 30 . L-palmitoylcarnitine has also been demonstrated to serve as a biomarker for diagnosis and prediction of clinical intrahepatic cholestasis in pregnant patients and those with persistent wheezing 31 . Acetylcarnitine and stearoylcarnitine are also closely related to β-oxidation and were depleted in the serum of epinephrine-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al found that serum levels of L-palmitoylcarnitine were signi cantly decreased in a rat model of myocardial infarction 30 . L-palmitoylcarnitine has also been demonstrated to serve as a biomarker for diagnosis and prediction of clinical intrahepatic cholestasis in pregnant patients and those with persistent wheezing 31 . Acetylcarnitine and stearoylcarnitine are also closely related to β-oxidation and were depleted in the serum of epinephrine-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…To date, metabolomic studies of childhood asthma have been mainly performed on blood, urine, and exhaled breath condensate samples. A study performed in BALs indicated that children with persistent wheezing had higher abundances of choline, oleamide, nepetalactam, butyrylcarnitine, l-palmitoylcarnitine, palmitoylethanolamide, and various phosphatidylcholines [13].…”
Section: Introductionmentioning
confidence: 99%